Attempts by the soviet regime to change the national identity of Lithuanians - Streikus, Arūnas (Genocidas ir rezistencija, 2007)
The article deals with the most important means used by the Soviet regime in order to change the national identity of the Lithuanians: the policy of historical memory and national-lin-guistic assimilation. With the help of documents from Soviet institutions and generalising previous historical research, an attempt is made to reveal the main directions of these efforts, and their aftermath.
Keywords: Soviet regime; national policy; russification; culture